Odpowiedzi

2010-01-26T09:57:25+01:00
2x+x=x(2+1)
3x²-6x=3x(x-2)
6x³+12x²=6x²(x+2)
x+2x-4x²=x(1+2-4x)
Najlepsza Odpowiedź!
2010-01-26T10:00:04+01:00
3a + 6b +12c = 3(a + 2b + 4c)
6x - 6 = 6(x - 1)
7x + 7y = 7(x + y)
1 5 1
2010-01-26T10:03:10+01:00
4a + 4b= 4(a + b )\\3x+15y= 3(x + 5y)\\7x+14y=7(x+2y)\\17x^2- 17 = x(x)\\py-p= p(y-p)\\9xy - y = 9x(y-y)

4a + 4b= 4(a + b )\\3x+15y= 3(x + 5y)\\7x+14y=7(x+2y)\\17x^2- 17 = x(x)\\py-p= p(y-p)\\9xy - y = 9x(y-y)

4a + 4b= 4(a + b )\\3x+15y= 3(x + 5y)\\7x+14y=7(x+2y)\\17x^2- 17 = x(x)\\py-p= p(y-p)\\9xy - y = 9x(y-y)

4a + 4b= 4(a + b )\\3x+15y= 3(x + 5y)\\7x+14y=7(x+2y)\\17x^2- 17 = x(x)\\py-p= p(y-p)\\9xy - y = 9x(y-y)

4a + 4b= 4(a + b )\\3x+15y= 3(x + 5y)\\7x+14y=7(x+2y)\\17x^2- 17 = x(x)\\py-p= p(y-p)\\9xy - y = 9x(y-y)

4a + 4b= 4(a + b )\\3x+15y= 3(x + 5y)\\7x+14y=7(x+2y)\\17x^2- 17 = x(x)\\py-p= p(y-p)\\9xy - y = 9x(y-y)

powinno byc dobrze...